2011
DOI: 10.1093/ndt/gfr588
|View full text |Cite
|
Sign up to set email alerts
|

Kidney and liver transplantation in patients with autosomal recessive polycystic kidney disease: a multicentric study

Abstract: Our data suggest that ARPKD patients evaluated for renal transplantation should be carefully screened for severe Caroli's disease. Even though the limited number of patients included in our study precludes any definite recommendation, pre-emptive liver transplantation may be a therapeutic option in ARPKD patients with severe Caroli's disease evaluated for renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…Among 78 patients in the USA, the 1-, 3-, and 5-year survival rates were 79.5, 75.5, and 75.5 %, respectively [1]. Similar percentages have been reported in single-center reports [50]. In our center, four of the 14 transplanted ARPKD patients had CLKT as the first operation, and five first underwent KT followed by CLKT at a later date.…”
Section: Long-term Outcomesupporting
confidence: 85%
See 1 more Smart Citation
“…Among 78 patients in the USA, the 1-, 3-, and 5-year survival rates were 79.5, 75.5, and 75.5 %, respectively [1]. Similar percentages have been reported in single-center reports [50]. In our center, four of the 14 transplanted ARPKD patients had CLKT as the first operation, and five first underwent KT followed by CLKT at a later date.…”
Section: Long-term Outcomesupporting
confidence: 85%
“…On the other hand, refractory complications of portal hypertension and recurrent cholangitis suggest CLKT as the first option (Table 3). Severe pathological findings of the liver (cirrhosis, large and infected biliary dilatations) and genotype (truncating mutations) also affect the treatment strategy [50]. Many of the children need KT later on, and simultaneous CLKT from the same donor probably provides better long-term kidney function than a sequential transplantation.…”
Section: Autosomal Recessive Polycystic Kidney Diseasementioning
confidence: 99%
“…97,98 Others have suggested earlier consideration of liver transplantation (LT) in ARPKD patients with severe liver disease who are being evaluated for kidney transplantation, even if they may not otherwise meet criteria for LT-based liver disease severity alone. 85,[98][99][100] In patients with liver-predominant disease who first undergo LT, acceleration of kidney disease progression is also a concern. 101 Currently, the only guidelines regarding listing for combined kidney-liver transplantation (CKLT) are in the context of end-stage liver disease due to hepatocellular dysfunction, for which listing for CKLT is recommended when estimated glomerular filtration rate is #30 mL/min/1.73m 2 .…”
Section: Dialysis and Transplantationmentioning
confidence: 99%
“…Studies in patients with ARPKD who underwent CKLT have reported patient survival rates of 70% to 100%. 99,103 …”
Section: Dialysis and Transplantationmentioning
confidence: 99%
“…The authors reason that the complications of hepatic involvement (predominantly the risk of ascending cholangitis) (19) coupled with improved outcomes of liver transplantation mandate a careful assessment of risk-benefit ratio in all ARPKD patients with severe dual organ involvement. The authors assert that lower Pediatric End Stage Liver Disease/Model for End Stage Liver Disease (PELD/MELD) scores can be used to justify the benefit of combined liver–kidney transplant compared with isolated kidney transplants.…”
Section: From Pathophysiology To Current and Future Therapies Pgd/ivfmentioning
confidence: 99%